2013
DOI: 10.1086/671772
|View full text |Cite
|
Sign up to set email alerts
|

Descent and Diffusion in Language Diversification: A Study of Western Numic Dialectology

Abstract: The two branches of Western Numic are the Mono and Northern Paiute languages. We argue that this taxonomic structure did not arise as usually assumed in historical linguistics, through increased di erentiation brought about by changes internal to each branch, but rather that di usion between Western and Central Numic played a crucial role in forming the Western Numic family tree. More generally, we suggest that di usion plays a greater role in language diversi cation than is usually recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…As Babel et al. note, diffusion of features had already been documented specifically for the Numic family (most recently in McLaughlin 2000); what this new research shows, however, is that diffusion did not involve a single phonological change, but rather a significant number of features across a well established boundary (Babel et al. forthcoming).…”
Section: Historical Research On Uto‐aztecan Languagesmentioning
confidence: 64%
See 1 more Smart Citation
“…As Babel et al. note, diffusion of features had already been documented specifically for the Numic family (most recently in McLaughlin 2000); what this new research shows, however, is that diffusion did not involve a single phonological change, but rather a significant number of features across a well established boundary (Babel et al. forthcoming).…”
Section: Historical Research On Uto‐aztecan Languagesmentioning
confidence: 64%
“…New diachronic research, as in the earliest Uto‐Aztecan tradition, continues to be driven by questions pertaining to the general mechanisms of linguistic change. An example of such a question is raised in Babel et al. (forthcoming): are shared innovations of related languages the result of descent from a common ancestor or rather the product of diffusion through already differentiated varieties?…”
Section: Historical Research On Uto‐aztecan Languagesmentioning
confidence: 99%
“…10 10 Diffusion of apparent regular sound changes leads one to question their usefulness in subgrouping. In a recent study of Western Numic dialects, Babel et al (2013) show that all In the discussion that follows, we will use the range of criteria in (1) to define areal sound patterns so as to ensure that the sound pattern in question is not likely to have resulted from (shared) inheritance, general linguistic tendencies, or chance. Though some of these criteria may prove too restrictive, eliminating some cases of areal sound patterns, they will provide us with a working base of areal patterns from which we may be able to extract interesting generalizations.…”
mentioning
confidence: 99%
“…Haspelmath ; Bowern , ) illustrates the debate regarding the extent to which horizontal transmission influences linguistic history. Consensus in the field supports the continued use of the family tree model, which may indeed interact with spatial diffusion of linguistic material (as in Babel et al ), though to a more limited extent than suggested by Dixon (). Model simulations conducted by Currie, Greenhill, and Mace () further demonstrate that phylogenetic comparative methods are able to infer ancestral character states, even in the presence of horizontal transmission.…”
Section: Continental and Subcontinental Scales: The Dynamics Of Changmentioning
confidence: 68%